European Vegetation Archive (EVA): an integrated database of European vegetation plots. Issue 1 (20th August 2015) - Chytrý, Milan; Hennekens, Stephan M.; Jiménez‐Alfaro, Borja; Knollová, Ilona; Dengler, Jürgen; Jansen, Florian; Landucci, Flavia; Schaminée, Joop H.J.; Aćić, Svetlana; Agrillo, Emiliano; Ambarlı, Didem; Angelini, Pierangela; et al.
Abstract: The European Vegetation Archive (EVA) is a centralized database of European vegetation plots developed by the IAVS Working Group European Vegetation Survey. It has been in development since 2012 and first made available for use in research projects in 2014. It stores copies of national and regional vegetation‐ plot databases on a single software platform. Data storage in EVA does not affect on‐going independent development of the contributing databases, which remain the property of the data contributors. EVA uses a prototype of the database management software TURBOVEG 3 developed for joint management of multiple databases that use different species lists. This is facilitated by the SynBioSys Taxon Database, a system of taxon names and concepts used in the individual European databases and their corresponding names on a unified list of European flora. TURBOVEG 3 also includes procedures for handling data requests, selections and provisions according to the approved EVA Data Property and Governance Rules. By 30 June 2015, 61 databases from all European regions have joined EVA, contributing in total 1 027 376 vegetation plots, 82% of them with geographic coordinates, from 57 countries. EVA provides a unique data source for large‐scale analyses of European vegetation diversity both for fundamental research and nature conservation applications. Updated information on EVA is available online athttp://euroveg.org/eva-database . Abstract : The European Vegetation Archive (EVA) was developed as a centralized database of European vegetation plots. By 30 June 2015, it included 61 contributing national or regional databases that in total contained 1 027 376 vegetation plots from 57 countries, 82% of them with geographical coordinates. EVA data are provided for various international projects of fundamental and applied research.